STRATEGIC-CONCEPTUAL PRINCIPLES OF MODERNIZATION OF THE SYSTEM OF SOCIAL SECURITY OF UKRAINE'S DEVELOPMENT IN THE CONDITIONS OF EUROPEAN INTEGRATION - OSIPOVA, LARISA; BILYK, VICTORIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to substantiate the theoretical provisions and develop practical recommendations for the formation of strategic and conceptual foundations for the modernization of the social security system of Ukraine in the context of European integration.It is shown that modern research and recommendations of domestic scientists are more partial than systemic, as they reveal and comprehend only certain aspects of the whole global complex of state social policy.The article emphasizes the urgency and critical timeliness of the formation and implementation of state policy to modernize the social security system, which is critical in the context of European integration aspirations to achieve the strategic goal of the social sphere of Ukraine with a high level of convergence with the European Union. A prospectus on external institutional priorities and priorities for realizing the internal potential of social growth has been implemented. The ascending preconditions for the formation of the policy of modernization of the social security system of Ukraine, in particular, systemic and characteristic, are determined.The applied significance of the research results is that the elements of strategizing the state policy of modernization of the social system of Ukraine in the conditions of globalization are determined. The institutional priorities of the national program of modernization of Ukraine's social security system have been identified, namely - formation of digital infrastructure and development of smart cities, development of green economy, security of consumption, establishment of resistant health care system, improvement of social responsibility of entrepreneurship and society. new forms of employment, achieving a clean and safe living space.The scientific novelty of the research results is the identification of strategic priorities of the state policy of modernization of the social security system for the development of the national economy in the context of globalization and European integration.
Keywords: social welfare; modernization of the social sphere; integration processes; globalization; economic space